Approaching Ideal Polyphase Filter Response in 65-nm CMOS - D. Martínez Pérez, Antonio; Morte, Jorge; Aznar, Francisco; Sánchez-Azqueta, Carlos; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2017)
This work analyzes the effect of the most critical non-idealities on a passive polyphase filter implemented in a 65-nm CMOS technology, to attain single-sideband transmission in a 5 GHz Wi-Fi alike communication system. Non-idealities impact on this kind of passive complex filter have not been thoroughly analyzed in literature.